2007
DOI: 10.1074/jbc.m607836200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of S6 Kinase 1 Activation by Phosphorylation at Ser-411

Abstract: Ribosomal S6 kinase 1 (S6K1), as a key regulator of mRNA translation, plays an important role in cell cycle progression through the G 1 phase of proliferating cells and in the synaptic plasticity of terminally differentiated neurons. Activation of S6K1 involves the phosphorylation of its multiple Ser/Thr residues, including the proline-directed sites (Ser-411, Ser-418, Thr-421, and Ser-424) in the autoinhibitory domain near the C terminus. Phosphorylation at Thr-389 is also a crucial event in S6K1 activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…We also investigated the role of p35 in neurite formation. In PC12 cultures, application of GW8510, a specific Cdk5 inhibitor compound of low cytotoxicity (41,42), effectively inhibited NGF-induced neurite outgrowth (Fig. 6, A and B), in agreement with the reported observations using roscovitine or the kinase-dead Cdk5 mutants (12,14,39,40).…”
Section: Effects Of P35 Phosphorylation On Its Microtubule-polymerizisupporting
confidence: 90%
“…We also investigated the role of p35 in neurite formation. In PC12 cultures, application of GW8510, a specific Cdk5 inhibitor compound of low cytotoxicity (41,42), effectively inhibited NGF-induced neurite outgrowth (Fig. 6, A and B), in agreement with the reported observations using roscovitine or the kinase-dead Cdk5 mutants (12,14,39,40).…”
Section: Effects Of P35 Phosphorylation On Its Microtubule-polymerizisupporting
confidence: 90%
“…Indeed, recent evidence has demonstrated that both CDK1 and CDK5 have the potential to phosphorylate S6K1 directly. In the case of CDK5, phosphorylation of S6K1 on Thr 411 has been demonstrated to be required for its phosphorylation and activation by mTOR, suggesting that such a feedback loop between CDK2 and S6K1 may exist in cycling T cells (58,59). That S6 is itself important for T cell proliferation has been established in mice expressing one defective allele for S6 (60).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of reporters can be used to quantify activity in this pathway; Abl‐mediated Cdk5/p35 activity, detected from the S6K‐pSer 411 immunoreactivity (Hou et al. 2007), was significantly different between WT and WIP −/− neurons (Fig. 3A and B).…”
Section: Resultsmentioning
confidence: 89%
“…2000; Hou et al. 2007). To test whether reduced Abl activity is responsible for the differences observed between WIP −/− and WT neurons, we cultured primary neurons from both genotypes alone, with the Abl inhibitor imatinib, or with DMSO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation